Phallus haitangensis, a new species of stinkhorn from Yunnan Province, China - Li, Huili; Ma, Xuelan; Mortimer, Peter E.; Karunarathna, Samantha C.; Xu, Jianchu; Hyde, Kevin D. (Phytotaxa, 2016)
Four specimens of Phallus were collected during surveys in a Pinus armandii forest in Baoshan, Yunnan Province, China. Macro- and micro-characteristics, together with Internal Transcribed Spacer (ITS) sequence data, showed that the four specimens belong to a new species, here named Phallus haitangensis. The ITS phylogenetic analyses, morphological descriptions, color photographs, and line drawings are provided, and compared with closely related species in the genus.